Numerical simulations of Pelton turbine flow to predict large head variation influence. Issue 1 (June 2021) - Alimirzazadeh, S; Decaix, J; Avellan, F; Crettenand, S.; Münch-Alligné, C.
Abstract: In the framework of the new feed-in-tariff system in Switzerland for Small Hydropower Plants (SHP), the aim of the SmallFLEX project, led by HES-SO Valais and performed in collaboration with EPFL, WSL, EAWAG, PVE, and FMV, is to show how SHP can provide winter peak energy and ancillary services, whilst remaining eco-compatible. The pilot and demonstrator site selected is the new small hydropower plant of Gletsch-Oberwald (KWGO) owned by FMV and commissioned end of 2017. This run-of-river power plant is equipped with two six-jet Pelton turbine units featuring a maximum power of 7 MW each. The addition of flexibility can be reached by using existing volumes of the power plant: the settling basin, the forebay chamber as well as part of the headrace tunnel. By consequence, the turbine head will undergo variations. To ensure that these variations will not cause any damages to the Pelton runner, the influence of the available head is investigated by numerical simulations. The simulations are carried out using two different software. OpenFOAM, which is based on a Finite Volume Method (FVM), is used for computing the flow inside the distributor until the jet. GPU-SPHEROS, which is based on Arbitrary Lagrangian-Eulerian (ALE) Finite Volume Particle Method (FVPM) is utilized to compute the interaction between the jet and Pelton buckets. Mixing the two aforementioned approaches, i.e. mesh-based FVM and particle-based FVPM, the overall torque T of the present six-jet Pelton runner can be reconstructed for different rated heads and discharges. The predicted torque fluctuations can then be considered for an estimation of the structural fatigue damage of the runner.